1993
DOI: 10.1111/j.1469-8137.1993.tb04533.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics and associated mycorrhizal fungi of little bluestem grass [Schizachyrium scoparium (Michx.) Nash] on burned and unburned sand prairies

Abstract: SUMMARYWe examined the influence of burning on little bluestem grass productivity and its vesicular-arbuscular mycorrhizal (VAM) fungal associates in a sand prairie community over four growing seasons (1986-9), Aboveand below-ground productivity was higher on the burned sites than on the unburned sites. Percent VAM fungal colonization levels were significantly lower on burned sites than on the unburned sites. In contrast, early in the growing season, colonized and specific root lengths were longer on the burne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…EM fungi colonise plant roots by forming an intercellular interface consisting of highly branched hyphae, while also forming a dense hyphal sheath, surrounding the root surface. This entire hyphal network aids in increasing root surface area (Smith & Read ), thus improving plant access to nutrients (Dhillion & Anderson ) and water (Lehto & Zwiazek ). Plant roots are colonised by one to many EM fungal species as they grow and encounter EM fungal spores or hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…EM fungi colonise plant roots by forming an intercellular interface consisting of highly branched hyphae, while also forming a dense hyphal sheath, surrounding the root surface. This entire hyphal network aids in increasing root surface area (Smith & Read ), thus improving plant access to nutrients (Dhillion & Anderson ) and water (Lehto & Zwiazek ). Plant roots are colonised by one to many EM fungal species as they grow and encounter EM fungal spores or hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, grazed pastures had both smaller fuel load and an increased number of 'patchy' areas, particularly in the pastures grazed by bison, resulting in less intense and incomplete burns in grazed compared with ungrazed pastures, as has been reported by others (England and DeVos, 1969;Hobbs, 1996;Knapp et al, 1999;Bakker et al, 2003). Mycorrhizal root colonization may decrease due to burning (Dhillon et al, 1988;Dhillon and Anderson, 1993). In contrast, increases in AMF colonization (Bentivenga and Hetrick, 1991) and spore abundance (Eom et al, 1999) have been reported as short-term burning effects on tallgrass prairie.…”
Section: Discussionmentioning
confidence: 77%
“…Mycorrhizal root colonization may decrease due to burning (Dhillon et al. , 1988; Dhillon and Anderson, 1993). In contrast, increases in AMF colonization (Bentivenga and Hetrick, 1991) and spore abundance (Eom et al.…”
Section: Discussionmentioning
confidence: 99%